Islamic Education in Responding to the Challenges of Cyberbullying in the School Environment - Muh. Ibnu sholeh; Siti Fatinnah binti Ab Rahman (International Journal of Islamic Pedagogical Research, 2025)
The problem of cyberbullying in Islamic school environments is increasingly prevalent alongside the rapid development of digital technology and the high use of social media among students. This phenomenon not only affects students’ psychological well-being but also reflects weak moral development in understanding digital ethics and humanitarian values. The purpose of this study is to analyze the role of Islamic educational institutions in preventing cyberbullying through the integration of Qur’anic values and Lawrence Kohlberg’s theory of moral development. This research employs a qualitative method with a literature review approach by examining various scholarly sources related to Islamic education, moral development, and cyberbullying prevention. The findings reveal that Islamic educational institutions hold a strategic role in enhancing students’ moral development—from the pre-conventional to the post-conventional level—through strengthening moral curriculum, cultivating digital ethics, promoting teacher role modeling, and integrating media literacy into learning activities. The implications of this study emphasize that cyberbullying prevention must be carried out in a preventive, systematic, and sustainable manner by creating an educational ecosystem grounded in spiritual, moral, and universal ethical values, thereby shaping a generation that is wise, civilized, and responsible in navigating the digital world.